Analisis Perbedaan Nilai Supply Overburden dari Truck dan Pit Crushing and Conveying (PCC) Pada Pit South Tutupan Periode Oktober – Desember 2016 di PT. Adaro Indonesia, Kalimantan Selatan - Teuku Raja Istiqhafar Surya; Haqul Baramsyah; Hendra Harisman (Journal of Geosciences, Mining Engineering, and Technology, 2022)
AbstractPT. Adaro Indonesia is a coal mining company in Indonesia which implements Pit Crushing and Conveying (PCC) for overburden removal. The implementation of the PCC due to overburden removal combines shovel and truck, crusher, and conveyor in the operating system. Trucks are needed as a supplier of overburden to pit crusher station of the PCC. By implementing this system, there has been a difference (deviation) between the value of overburden supplied by truck and the value of overburden received (detected) by PCC. Based on the issue, an analysis is needed to minimize the deviation and to determine the accuracy of deviation supply of truck and PCC. This research was conducted to solve the problem by observing and analysing the factors that cause the difference (deviation) of the overburden supply value. The results of this research defines that the value of overburden received (detected) by PCC is generally higher than the value of overburden supplied by truck with a deviation in the range of 11% to 37%. The deviation can be minimized by using the density value corresponding to the overburden, by changing the calculation method of truck production and PCC production, and by establishing the accuracy deviation supply to truck and PCC.